2017
DOI: 10.1007/s12325-017-0511-1
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-Dose Triple Combination of Antihypertensive Drugs Improves Blood Pressure Control: From Clinical Trials to Clinical Practice

Abstract: Introduction: Blood pressure (BP) control is the main clinical goal in the management of hypertensive patients; however, BP in most of these patients remains uncontrolled, despite the widespread availability of antihypertensive drugs as free-combination therapy. This study compared the efficacy of a fixed-dose triple combination (FDTC) of antihypertensive drugs with that of a free combination of three antihypertensives in patients with uncontrolled hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 38 publications
1
28
0
4
Order By: Relevance
“…In agreement with previous reports, the present study found that triple therapy with ARBs, ACE inhibitors, and CCBs had a good safety profile, and no correlation of this triple therapy with a low DBP or diastolic hypotension has been reported [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous reports, the present study found that triple therapy with ARBs, ACE inhibitors, and CCBs had a good safety profile, and no correlation of this triple therapy with a low DBP or diastolic hypotension has been reported [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…The reduction in blood pressure with combined drugs was approximately 5 times greater than doubling the dose of one drug [6,22]. In a recent study [23], blood pressure control with a fixed-dose triple combination therapy was superior to the free combination of the three drugs (perindopril/indapamide/amlodipine). Combination therapy seems to be mandatory to reach target blood pressure; the average number of drugs required to reach blood pressure goals amounted to more than 3 in trials focusing on cardiovascular morbidity and mortality [24].…”
Section: Discussionmentioning
confidence: 95%
“…SPCs were exclusively used in only 34% of patients, while in the remaining 66% of patients the combinations used were either free (39%) or comprised both SPC and free components (27%). The use of SPCs, as compared to their free-drug counterparts, has been shown to be associated with a significant higher adherence rate to treatment [ 19 22 ] and lower health-care costs [ 20 ], while a non-significant reduction in blood pressure [ 19 ] but a significant improved blood pressure control rate [ 21 , 23 ] were reported. High adherence to antihypertensive treatment has been shown to be related to lower cardiovascular events [ 24 27 ].…”
Section: Discussionmentioning
confidence: 99%